Стан антиоксидантної системи у Aylostera flavistyla F. Ritt., Echinocactus grusonii Hildm. та Mamillaria bocasana Pos. (Cactaceae) за умов гіпертермії - Nuzhyna, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
Data about lipid peroxidation and changing peroxidase and superoxidedismutase activity in annuals non-hardened plant stems of Aylostera flavistyla F. Ritt., Echinocactus grusonii Hildm. and Mamillaria bocasana Pos. (Cactaceae) under exposure to high temperatures (+40 or 50 °C) for three hours. Different mechanisms of adaptation to hyperthermia studied species at the biochemical level were revealed. Sharp temperature increase to 40 °C is stress for annuals plants A. flavistyla, E. grusonii and M. bocasana. Antioxidant protection when the temperature stress is most intense in E. grusonii, to a greater extent by peroxidase. The superoxide dismutase in stress in the studied species is reduced. The least resistant plants were hyperthermia A. flavistyla.